Pengaruh IPM dan Laju Pertumbuhan PDRB terhadap Persentase Penduduk Miskin Di Kabupaten Karo Tahun 2011-2019 - Reavindo, Quarthano (Syntax Idea, 2021)
This study aims to see how the influence of the Human Development Index (HDI) and the growth rate of Gross Regional Domestic Product (GRDP) on the percentage of poor people in Karo Regency in the period 2011-2019. This study uses quantitative research methods with multiple linear regression analysis methods. The results of this study indicate that the influence of the Human Development Index (HDI) variable and the Gross Regional Domestic Product (GRDP) growth rate on the percentage of poor people is 72 percent while the remaining 22 percent is affected. by factors other than the model. Simultaneously the Human Development Index (HDI) variable and the growth rate of the Gross Regional Domestic Product (GRDP) have a significant effect on the percentage of the poor. Partially the Human Development Index (HDI) variable has a negative and insignificant effect on the percentage of poor people, while the growth rate of Gross Regional Domestic Product (PDRB) has a positive and significant effect on the percentage of poor people.